Low-grade systemic inflammation, but not neuroinflammation, is associated with 12-month postoperative outcome after total hip arthroplasty in patients with painful osteoarthritis: an explorative study - Morten R. Blichfeldt-Eckhardt; Claus Varnum; Jørgen T. Lauridsen; Lasse E. Rasmussen; Winnie C. P. Mortensen; Hanne I. Jensen; Henrik B. Vaegter; Kate L. Lambertsen (Bone & Joint Research)
Aims: Better prediction of outcome after total hip arthroplasty (THA) is warranted. Systemic inflammation and central neuroinflammation are possibly involved in progression of osteoarthritis and pain. We explored whether inflammatory biomarkers in blood and cerebrospinal fluid (CSF) were associated with clinical outcome, and baseline pain or disability, 12 months after THA. Methods: A total of 50 patients from the Danish Pain Research Biobank (DANPAIN-Biobank) between January and June 2018 were included. Postoperative outcome was assessed as change in Oxford Hip Score (OHS) from baseline to 12 months after THA, pain was assessed on a numerical rating scale, and disability using the Pain Disability Index. Multiple regression models for each clinical outcome were included for biomarkers in blood and CSF, respectively, including age, sex, BMI, and Kellgren-Lawrence score. Results: Change in OHS was associated with blood concentrations of tumour necrosis factor (TNF), interleukin-8 (IL-8), interleukin-6 receptor (IL-6R), glycoprotein 130 (gp130), and IL-1β (R2 = 0.28, p = 0.006), but not with CSF biomarkers. Baseline pain was associated with blood concentrations of lymphotoxin alpha (LTα), TNFR1, TNFR2, and IL-6R (R2 = 0.37, p < 0.001) and CSF concentrations of TNFR1, TNFR2, IL-6, IL-6R, and IL-1Ra (R2 = 0.40, p = 0.001). Baseline disability was associated with blood concentrations of TNF, LTα, IL-8, IL-6, and IL-1α (R2 = 0.53, p < 0.001) and CSF concentrations of gp130, TNF, and IL-1β (R2 = 0.26, p = 0.002). Thus, preoperative systemic low-grade inflammation predicted 12-month postoperative outcome after THA, and was associated with preoperative pain and disability. Conclusion: This study highlights the importance of systemic inflammation in osteoarthritis, and presents a possible path for better patient selection for THA in the future. Preoperative central neuroinflammation was associated with preoperative pain and disability, but not change in OHS after THA. Cite this article: Bone Joint Res 2024;13(12):741–749.